(3l+4)+(3-m)i=16-31

Simple and best practice solution for (3l+4)+(3-m)i=16-31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3l+4)+(3-m)i=16-31 equation:


Simplifying
(3l + 4) + (3 + -1m) * i = 16 + -31

Reorder the terms:
(4 + 3l) + (3 + -1m) * i = 16 + -31

Remove parenthesis around (4 + 3l)
4 + 3l + (3 + -1m) * i = 16 + -31

Reorder the terms for easier multiplication:
4 + 3l + i(3 + -1m) = 16 + -31
4 + 3l + (3 * i + -1m * i) = 16 + -31
4 + 3l + (3i + -1im) = 16 + -31

Reorder the terms:
4 + 3i + -1im + 3l = 16 + -31

Combine like terms: 16 + -31 = -15
4 + 3i + -1im + 3l = -15

Solving
4 + 3i + -1im + 3l = -15

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + 3i + -1im + -4 + 3l = -15 + -4

Reorder the terms:
4 + -4 + 3i + -1im + 3l = -15 + -4

Combine like terms: 4 + -4 = 0
0 + 3i + -1im + 3l = -15 + -4
3i + -1im + 3l = -15 + -4

Combine like terms: -15 + -4 = -19
3i + -1im + 3l = -19

Add '-3l' to each side of the equation.
3i + -1im + 3l + -3l = -19 + -3l

Combine like terms: 3l + -3l = 0
3i + -1im + 0 = -19 + -3l
3i + -1im = -19 + -3l

Reorder the terms:
19 + 3i + -1im + 3l = -19 + -3l + 19 + 3l

Reorder the terms:
19 + 3i + -1im + 3l = -19 + 19 + -3l + 3l

Combine like terms: -19 + 19 = 0
19 + 3i + -1im + 3l = 0 + -3l + 3l
19 + 3i + -1im + 3l = -3l + 3l

Combine like terms: -3l + 3l = 0
19 + 3i + -1im + 3l = 0

The solution to this equation could not be determined.

See similar equations:

| (-3)+2x=(-x)+6 | | 3x-11-2x=-3 | | X+6=3x-2(x-3) | | 4x-6=-x+54 | | y=2lx-2l+7 | | f-27=4f | | -3x=19-4 | | .10(x-4)+.02x=.06x-.7 | | -12=3x-5x | | 8t^2-19t+11=0 | | -6x-6=3x-15 | | y=sqrt-9-2 | | 209=19*11+13n | | 3y^3-193=0 | | 6-8n=0 | | (X-3)(x+4)-30=0 | | 8x-5-2x+5=18+8x | | -6x+3=-45+2x | | 5+24=x+8 | | 3(y-10)+1=6(y-8) | | -4x+8=-2+x | | 5-5z=-3z | | x+3=-26+15 | | -8.2-1.7= | | 4x+2(14-x)=40 | | X=-0.142+-0.285(10.90) | | -10+x=-x+12 | | 23=b+s | | 5x(10)=81 | | N(10)+N(5)+N(0)+N(23)+N(10)= | | 15=51c-13 | | 35=-6t-7 |

Equations solver categories